Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Belanja Modal: Studi Kasus pada Pemerintah Kota Subulussalam - Fitri; Cici Darmayanti; Linda Rahmazaniati; Sari Maulida Vonna (Medan Resource Center, 2025)
This study examines the influence of Regional Original Revenue (Pendapatan Asli Daerah / PAD) and Balancing Funds on capital expenditure in Subulussalam City. The implementation of regional autonomy has significantly transformed local governance by granting greater authority and responsibility to regional governments in managing development and public finance. One of the major challenges faced by local governments concerns their capacity to finance public expenditures and prioritize development programs that directly benefit society, particularly through capital expenditure allocation. This study addresses the question of whether PAD and Balancing Funds significantly affect capital expenditure in Subulussalam City. The research employed a descriptive quantitative approach using secondary data obtained through documentation methods from the Regional Financial Management Agency (BPKD) of Subulussalam City for the 2019–2023 period. Data were analyzed using multiple linear regression techniques. The findings reveal that PAD and Balancing Funds partially influence capital expenditure. Simultaneously, both variables demonstrate a positive and significant effect on capital expenditure, as indicated by significance values below 0.05. The study concludes that strengthening regional revenue capacity and optimizing balancing fund allocation are essential for improving regional development through sustainable capital expenditure policies.